Solve for y:

\(\displaystyle{3}{x}-{6}{y}={12}\)

First subtract 3x from both sides:

\(\displaystyle-{6}{y}={12}-{3}{x}\)

Now divide everything by -6:

\(\displaystyle{y}=-\frac{{12}}{{6}}+\frac{{3}}{{6}}{x}\)

Finally simplify:

\(\displaystyle{y}=-{2}+\frac{{1}}{{2}}{x}\)

Then rewrite this as:

\(\displaystyle{y}=\frac{{1}}{{2}}{x}-{2}\)

\(\displaystyle{3}{x}-{6}{y}={12}\)

First subtract 3x from both sides:

\(\displaystyle-{6}{y}={12}-{3}{x}\)

Now divide everything by -6:

\(\displaystyle{y}=-\frac{{12}}{{6}}+\frac{{3}}{{6}}{x}\)

Finally simplify:

\(\displaystyle{y}=-{2}+\frac{{1}}{{2}}{x}\)

Then rewrite this as:

\(\displaystyle{y}=\frac{{1}}{{2}}{x}-{2}\)